Species list and conservation priority of butterflies (Lepidoptera, Rhopalocera) in Dong Van karst plateau, Ha Giang - Lien, Vu Van (Academia Journal of Biology, 2015)
Study species and conservation priority of butterflies in Dong Van Karst Plateau, Ha Giang province was carried out in forests of Lung Cu, Pho Bang, Ta Phin and sites near Dong Van centre. The habitats are the natural forest on mountain, the secondary forest, the forest edge, shrub and grass from 1,400 to 1,700 m a.s.l. The study was carried out sometimes from May to September from in 2008, 2010 and 2011. Total 132 species of 8 butterfly families were recorded during studied period. Two species listed in the Red Data Book of Vietnam and CITES are Troides aeacus and Teinopalpus imperialis. There are 33 species with individuals 1-2 (25% of all species), 44 species with individuals 3-5 (33% of all species), 14 species with individuals 6-10 (11% of all species), and 41 species with individuals more than 10 (31% of all species). Butterfly species of Dong Van karst plateau consists of 12.6% of all butterfly species of Vietnam, but the family Papilionidae of Dong Van karst plateau consists of 40% of all species of the family of Vietnam. The family Papilionidae is very important for conservation of insects. Some species distributed in Vietnam merely found in the studied area are Byasa hedistus, Papilio elwesi, Sasakia funeblis, S. charonda, and Melitaea yuenty. These species are rare and distribute in forests where forests are being declined. So it is needed conservation meseasures to conserve, especially conserve the natural forests in Dong Van karst plateau, the habitat of these butterflies.